2013
DOI: 10.1016/j.solener.2012.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between textured SnO2:F and Mo contacts with the p-type layer in p–i–n hydrogenate amorphous silicon solar cells by forward bias impedance analysis

Abstract: In this paper we compare the performance of the textured SnO 2 :F and Mo contacts with the p-type layer in p-in hydrogenate amorphous silicon (a-Si:H) solar cells. We use standard current-voltage (I-V) electrical characterization methods coupled with forward bias small signal impedance analysis. We show the efficacy of this technique to determine the effective carrier lifetime in photovoltaic cells. We show that such effective lifetimes are indeed directly connected to the respective dark diode saturation curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To test such concept we have performed reverse bias stress experiments in samples in which the TCO layer in contact with the p-type a-Si: H film has been replaced by a Mo film, in cells realized as described in the previous section. The use of Mo can give some advantage for the p-type a-Si:H/metal contact resistance and for the solar cell carrier lifetime (compared to FTO) [10,11], and it may be advantageous to fabricate a-Si:H solar cells on flexible substrates [12], and to realise plasmonic light trapping [21]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test such concept we have performed reverse bias stress experiments in samples in which the TCO layer in contact with the p-type a-Si: H film has been replaced by a Mo film, in cells realized as described in the previous section. The use of Mo can give some advantage for the p-type a-Si:H/metal contact resistance and for the solar cell carrier lifetime (compared to FTO) [10,11], and it may be advantageous to fabricate a-Si:H solar cells on flexible substrates [12], and to realise plasmonic light trapping [21]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the cells with Mo bottom contact the efficiencies were typically about 5% with open-circuit voltage of 0.85 V, short-circuit current densities of 12 mA/cm 2 and fill factor of 47%. The differences between these two types of cells are discussed in detail in references [10][11][12] and they are attributed to differences in substrate texture and photocarrier lifetime.…”
Section: Methodsmentioning
confidence: 99%
“…According to literature reports, in the forward bias condition, the carrier lifetime at the Mo/ptype a-Si:H interface is longer than that at the transparent conductive oxide (TCO)/p-type a-Si:H interface. 18,19 In other words, the carrier recombination rate in the former is lower than that in the latter. It was also reported that the ITO electrode usually forms ohmic contact with both p-type and n-type a-Si:H films.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, the analyses of size, structure and morphology of the thin layers are important to fulfil the above said requirements. Recently, large efforts have been put on the manufacturing of thin films to improve the efficiency of amorphous and microcrystalline silicon based solar cells [1][2][3][4][5][6]. The main intention on the development of such materials in solar industry (3 rd generation of solar cells) is to reduce the usage of materials and deposition costs, and also to increase the efficiency of the photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%